VDGA-Based Resistorless Mixed-Mode Universal Filter and Dual-Mode Quadrature Oscillator - Orapin Channumsin; Jetwara Tangjit; Tattaya Pukkalanun; Worapong Tangsrirat (Applied Sciences, 2025)
This study introduces an electronically tunable resistorless mixed-mode universal filter and dual-mode quadrature oscillator configuration utilizing merely two voltage differencing gain amplifiers and two grounded capacitors. The suggested filter can perform all generic biquadratic filter functions in all four modes: voltage mode, trans-admittance mode, current mode, and trans-impedance mode, while utilizing the same design. The pole frequency and the quality factor can be tuned electronically and orthogonally by means of the transconductances of the voltage differencing gain amplifier. The dual-mode quadrature oscillator featuring both voltage and current outputs can also be obtained from the proposed filter core. It additionally provides separate electronic control of the oscillation condition and frequency. Several PSPICE simulations with the TSMC 0.18 μm CMOS model confirm the feasibility of the proposed configurations. Both proposed circuits were experimentally evaluated using commercially available integrated circuit LM13600s. Both simulation and experimental results have validated the performance of the design.
Keywords: Analog and Mixed-Signal Circuit Design; Advancements in PLL and VCO Technologies; Advanced Adaptive Filtering Techniques